Crude palm oil is one of export comodities of Indonesia. Theme, it is of crucial importance to improve the quality of crude palm oil (CPO) through the process of CPO production. This paper discusses the design and implementation of an automatic process control for crude palm oil clarification. The automatic control system proposed herein is suppoded by a computer which performs intensive computation to determine the correct volume of water required for a CPO clarification process. The computer i - Lloyd .; Kudang B Seminar; Purboyo Guritno (Jurnal Keteknikan Pertanian, 1997)
Crude palm oil is one of export comodities of Indonesia. Theme, it is of crucial importance to improve the quality of crude palm oil (CPO) through the process of CPO production. This paper discusses the design and implementation of an automatic process control for crude palm oil clarification. The automatic control system proposed herein is suppoded by a computer which performs intensive computation to determine the correct volume of water required for a CPO clarification process. The computer is also used to monitor and maintain a desired temperature during the process. The implementation results indicate promising performance of the system control.